Effects of the sea-level changes on a wave-worked Gilbert-Type delta (Late Pliocene, Aguilas Basin, SE Spain) - Zazo, Caridad; Bardaji, T.; Dabrio, CRISTINO J.; Goy, José Luis (Cuadernos de Geología Ibérica, 1991)
Sin resumen